Interventional treatments for chronic, axial or radicular, non-cancer, spinal pain: a protocol for a systematic review and network meta-analysis of randomised trials - Xiaoqin Wang; Jason W Busse; Behnam Sadeghirad; Gordon H Guyatt; Thomas Agoritsas; Ivan D Florez; Yaping Chang; Elena Kum; Y Raja Rampersaud; D Norman Buckley; Andrea J Darzi; Grace Martin; et al. (BMJ Open)
Introduction Chronic, non-cancer, axial or radicular spinal pain is a common condition associated with considerable socioeconomic burden. Clinicians frequently offer patients various interventional procedures for the treatment of chronic spine pain; however, the comparative effectiveness and safety of available procedures remains uncertain.Methods We will conduct a systematic review of randomised controlled trials that explores the effectiveness and harms of interventional procedures for the management of axial or radicular, chronic, non-cancer, spine pain. We will identify eligible studies through a systematic search of Medline, EMBASE, CINAHL, Cochrane Central Register of Controlled Trials and Web of Science from inception without language restrictions. Eligible trials will: (1) enrol primarily adult patients (≥18 years old) with axial or radicular, chronic, non-cancer, spine pain, (2) randomise patients to different, currently available, interventional procedures or to an interventional procedure and a placebo/sham procedure or usual care, and (3) measure outcomes at least 1 month after randomisation.Pairs of reviewers will independently screen articles identified through searches and extract information and assess risk of bias of eligible trials. We will use a modified Cochrane instrument to evaluate risk of bias. We will use frequentist random-effects network meta-analyses to assess the relative effects of interventional procedures, and five a priori hypotheses to explore between studies subgroup effects. We will use the Grading of Recommendations Assessment, Development and Evaluation approach to assess the certainty in evidence for each outcome, including direct, indirect and network estimates.Ethics and dissemination No research ethics approval is required for this systematic review, as no confidential patient data will be used. We will disseminate our findings through publication in a peer-reviewed journal and conference presentations, and our review will support development of a BMJ Rapid Recommendations providing contextualised clinical guidance based on this body of evidence.PROSPERO registration number CRD42020170667.